1999
DOI: 10.1007/bf02738069
|View full text |Cite
|
Sign up to set email alerts
|

Expression, regulation, and function of the SPR family of proteins

Abstract: The small, proline-rich (SPR) genes consist of three subclasses closely linked on human chromosome 1, a region referred to as the epidermal differentiation complex. SPR genes consist of two exons, with the second exon containing the entire open reading frame. SPRs are expressed in all squamous tissues of the skin, scalp, footpad, vaginal epithelia, and most of the epithelial lining of the digestive tract, including the lip, tongue, esophagus, and forestomach. Although SPR1 is absent in normal mucociliary epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 44 publications
2
73
0
Order By: Relevance
“…It was reported that the SPRR1 protein played a role in the nucleus and was associated with G0 entering of the cell cycle, and SPRR2 expression was reversely related to the proliferation state in the keratinocyte, partially due to the activation of p27, p21 and p16 Ink4α [24][25][26][27]. Under the effects of cycling steroid hormones, uterine luminal and glandular epithelial cells have higher mitotic rates at the diestrous and proestrous stages, and undergo apoptosis at the estrous and metestrous stages [28].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the SPRR1 protein played a role in the nucleus and was associated with G0 entering of the cell cycle, and SPRR2 expression was reversely related to the proliferation state in the keratinocyte, partially due to the activation of p27, p21 and p16 Ink4α [24][25][26][27]. Under the effects of cycling steroid hormones, uterine luminal and glandular epithelial cells have higher mitotic rates at the diestrous and proestrous stages, and undergo apoptosis at the estrous and metestrous stages [28].…”
Section: Discussionmentioning
confidence: 99%
“…The products of these genes contribute to the cellular envelope of squamous epithelial cells, which decreases epithelial permeability and perhaps increases epithelial rigidity (64,65). In addition, SPRR proteins have been reported to migrate to the nucleus and influence gene expression and cellular differentiation (66). Both of these effects may influence airway responsiveness, and the latter effect has the potential to influence goblet cell differentiation and mucus production.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulated genes included also stromelysin-1/ matrix metalloproteinase-3 (MMP-3), a proteinase with strong involvement in tumor development (Sternlicht et al, 2000) and the serine protease BSSP, which is robustly induced in the skin by treatment with the tumor promoter phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA; Breitenbach et al, 2001). Furthermore, transcripts for keratin 6 and keratin 16, which are associated with epithelial hyperproliferation as well as for small proline-rich proteins (Sprr) associated with keratinocyte differentiation and epithelial barrier function (Tesfaigzi and Carlson, 1999;Chu and Weiss, 2002) were up-regulated.…”
Section: Transcriptional Profiling Reveals Activation Of Inflammatorymentioning
confidence: 99%